Tourism Impact Of Forest Fires In The Aek Martua Waterfall Area, Rokan Hulu Regency, Riau - Niethzie Trie Revaliza Mj (Institut Seni Indonesia Padangpanjang, 2025)
The Aek Martua Waterfall area in Rokan Hulu, Riau, is one of the region’s prominent natural tourist destinations, renowned for its tiered waterfalls and well-preserved forest environment. However, the forest fire that occurred in July 2025 had a significant impact on the sustainability of tourism in this area. This study aims to examine the post-fire condition of tourism at Aek Martua Waterfall, including environmental impacts, changes in visitor numbers, and the effects on the local community’s economy. Previous research describes ecotourism as a form of tourism conducted in natural environments, emphasizing minimal negative environmental impact and providing socio-economic benefits for local communities. Additionally, ecotourism is considered a nature-based tourism sector that supports sustainable development (Nugroho, 2015). This study employs a qualitative research method through literature review and field observation. The findings indicate that the forest fire caused severe ecological damage, including the loss of part of the Tahura forest area, destruction of natural ecosystems, and a decline in the visual quality and attractiveness of the destination. These conditions negatively affected visitor comfort and safety. Despite this, some positive impacts were observed, such as improved accessibility to the tourist site; however, the ecological damage outweighs these benefits, making comprehensive recovery efforts essential. The results highlight the importance of sustainable environmental management, enhanced monitoring and education to prevent forest fires, and the development of conservation-based tourism to ensure the long-term sustainability of Aek Martua as a natural destination